Stable Isotope Constraints on Genetic Models for Gold-Quartz, Antimony-Gold-Quartz, Tin and Tungsten-Tin Mineralization, Hodgkinson Province, Northern Queensland - Bultitude R. J; Peters S. G; Myers I. A; Dowling K (The Australasian Institute of Mining and Metallurgy, 1990)
Gold-quartz and antimony-gold-quartz veins in the Hodgkinson Province are hosted by subgreenschist to greenschist facies metasediments and show no spatial association with granitic rocks. They commonly parallel axial plane foliations or occur in brittle to brittle-ductile shear zones. Detailed mapping in the Hodgkinson goldfield indicates that vein systems are isolated in distinct structural and lithologic domains by post-mineralization faulting. Gold-quartz and antimony-gold-quartz veins have distinctive mesoscopic textures characteristic of the mesothermal vein environment. Some of the antimony-gold-quartz veins are located on domain boundaries which truncate the gold mineralization. In. some areas, tin and tungsten-tin mineralization which are spatially related to Late Palaeozoic granitoids appear to postdate the gold-quartz and antimony-gold-quartz mineralization.Oxygen and hydrogen isotopic studies of vein and alteration assemblages associated with these diverse ores provide constraints on fluid sources and have implications for the origin of mesothermal gold mineralization. The available isotopic data are consistent with a dominantly magmatic source for tin and tungsten-tin mineralization although there is evidence of a late-stage meteoric component in some tin-mineralizing systems. Although a distal magmatic contribution cannot be entirely discounted, the gold-quartz and antimony-gold-quartz veins were probably deposited from deeply